CULTURAL TRANSFORMATION AND REVITALIZATION IDENTITY OF BANTEN JAWARA - Sururi, Ahmad; Mardiana, Siska; Putri, Liza Diniarizky (Faculty of Humanities, Diponegoro University, 2020)
Structurally and culturally, the identity and role of Banten Jawara are still very powerful and still exist in the circle of Banten bureaucratic power, giving rise to the public's negative views and image of the champion's identity. The purpose of this paper was to analyze the idea of cultural transformation and revitalization of the values of the local wisdom of Banten Jawara and the deconstruction of the identity of the champion as a Banten subculture. The study method used a qualitative descriptive approach. The data in this study consisted of primary data and secondary data. Primary data were obtained from observations in the field and interviews through direct interaction with key informants determined by purposive sampling technique. Secondary data were obtained through various searches of data relevant to the study from various literature such as journals, books, print and electronic media to support data analysis and described in the form of data narration. The stages of data analysis consisted of: sorting data, presenting data and conclusions. The results showed that the process of transformation and revitalization of Banten Jawara by repositioning the structur of champion institutions as cultural products and representations of cultural communication, while in the deconstruction process, it was rebuild the identity of Banten Jawara, so that society has the same view through peaceful tolerance and coexistence; the creation of social cohesion through the acceptance of local and national cultural identities with various individual, sectarian and communal differences; and has the willingness to resolve non-violent disputes; have community institutions that bind communities across groups; and place past violations as inheritance and serve as learning for current and future generations. The transformation and revitalization of Banten Jawara as the power of the social and cultural sub-culture of Banten is a continuous and continuous idea and perspective.